2011
DOI: 10.3390/molecules16087171
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Enzymatic Synthesis of Hesperidin Fatty Acid Esters in a Two-Phase System Containing Ionic Liquid

Abstract: Response surface methodology (RSM) based on a five-level, three-variable central composite design (CCD) was employed for modeling and optimizing the conversion yield of the enzymatic acylation of hesperidin with decanoic acid using immobilized Candida antarctica lipase B (CALB) in a two-phase system containing[bmim]BF4. The three variables studied (molar ratio of hesperidin to decanoic acid, [bmim]BF4/acetone ratio and lipase concentration) significantly affected the conversion yield of acylated hesperidin der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Our research group reported that, for the acylation of hesperidin with decanoic acid catalyzed by CALB, when the water content of the reaction medium increased from < 200 ppm to higher than 550 ppm, the conversion rate decreased from 39.7 to 14.0 % (▶ Fig. 6) [32].…”
Section: Factors That Influence the Flavonoid Acylation Reactionsmentioning
confidence: 95%
See 4 more Smart Citations
“…Our research group reported that, for the acylation of hesperidin with decanoic acid catalyzed by CALB, when the water content of the reaction medium increased from < 200 ppm to higher than 550 ppm, the conversion rate decreased from 39.7 to 14.0 % (▶ Fig. 6) [32].…”
Section: Factors That Influence the Flavonoid Acylation Reactionsmentioning
confidence: 95%
“…Our study research group recently reported the optimization of this process by Response Surface Methodology. The conversion rate of hesperidin to its ester (hesperidin decanoate) in the optimized conditions was 55.0 % [32].…”
Section: Synthesis Of Flavonoid Esters Using Lipasesmentioning
confidence: 98%
See 3 more Smart Citations